Lymphocyte B and T cell subsets in peripheral blood from patients with asbestosis. Issue 2 (February 1993) - Peng, L; Wang, X
Abstract : Peripheral blood lymphocytes were analysed by indirect staphylococcus protein A (SPA) rosette assay using monoclonal antibodies that identify B cells, total T cells (OKT3+), helper-inducer T cells (OKT4+), and suppressor-cytotoxic T cells (OKT8+). The purpose of this investigation was to determine the characteristics of lymphocyte B and T subsets in peripheral blood, and the relation of the changes to radiographic abnormalities in workers exposed to asbestos.